2020
DOI: 10.1097/ijg.0000000000001487
|View full text |Cite
|
Sign up to set email alerts
|

Disc Hemorrhages Are Associated With the Presence and Progression of Glaucomatous Central Visual Field Defects

Abstract: In this prospective cohort study, disc hemorrhages were associated with more severe central damage on 24-2 and 10-2 visual fields (VFs), and faster progression globally on 24-2 VFs and centrally on 10-2 VFs. Purpose: To study the relationship between disc hemorrhage (DH) and the presence and progression of glaucomatous central VF damage. Methods: Cross-sectional and longitudinal analyses were performed on data from the African Descent and Glaucoma Evaluation Study (ADAGES) cohort. Two masked investigators revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…3 4 However, the underlying etiology of DHs has remained elusive, and it is presently unclear if DHs are the cause or the consequence of glaucoma progression. 5,6 Prior studies investigating DHs and glaucoma progression have tended to focus on single glaucoma testing modalities (disc photographs, 7,8 visual fields, [9][10][11] or optical coherence tomography 12,13 ). A number of studies have demonstrated that presence of a DH leads to a greater probability of visual field progression and more severe central damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 4 However, the underlying etiology of DHs has remained elusive, and it is presently unclear if DHs are the cause or the consequence of glaucoma progression. 5,6 Prior studies investigating DHs and glaucoma progression have tended to focus on single glaucoma testing modalities (disc photographs, 7,8 visual fields, [9][10][11] or optical coherence tomography 12,13 ). A number of studies have demonstrated that presence of a DH leads to a greater probability of visual field progression and more severe central damage.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated that presence of a DH leads to a greater probability of visual field progression and more severe central damage. [9][10][11] Akagi and colleagues demonstrated that rates of retinal nerve fiber layer (RNFL) thinning were significantly faster in DH quadrants that non-DH quadrants and accelerated after DH occurred. 12 Similarly, ganglion cell-inner plexiform layer thinning rate was significantly more rapid in glaucomatous eyes with DH than in control eyes.…”
Section: Introductionmentioning
confidence: 99%
“…We performed linear regression analysis to obtain the slope of the change of MD of the VF. We defined progression on 24-2 and 10-2 VF when the magnitude of MD slope was worse than − 1.0 dB per year with P ≤ 0.05 based on previous study 40 43 . Initial paracentral scotomas were classified according to their progression pattern on 10-2 VF.…”
Section: Methodsmentioning
confidence: 99%
“…(42) Other studies have suggested that central visual field loss is accelerated in glaucomatous eyes with a disc hemorrhage. (43,44) An et al reported that high frequency disc hemorrhages in the same sector of the optic disc have been associated with significantly worse visual field progression compared to those patients with fewer disc hemorrhages, (45) whereas de Beaufort et al did not find difference in the rate of visual field progression in patients with a single disc hemorrhage versus those with recurrent disc hemorrhages. (46) In summary, there is good consensus that patients with ODHs are at higher risk of visual field deterioration, however, there is great variability in the rate or absolute number of patients who progress after a single or even multiple recorded episodes of ODHs.…”
Section: Disc Hemorrhagementioning
confidence: 99%